2020
DOI: 10.5937/bastina30-25930
|View full text |Cite
|
Sign up to set email alerts
|

Integrated teaching in modern primary schools

Abstract: Филозофски факултет Ниш Департман за педагогију ИНТЕГРАТИВНА НАСТАВА У САВРЕМЕНОЈ ОСНОВНОЈ ШКОЛИ Апстракт: Циљ рада се односи на студиозно проучавање и анализирање интегративне наставе, начина организације као и њеноg значајa у савремној основношколској настави. Имајући у виду чињеницу да се у савременој основној школи све више говори о потреби међудисциплинарног знања, које се базира на интегративним и синтетичким процесима, ова тема постаје веома актуелна и интересантна за стручњаке различитих профила. Интег… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Some teachers suggested that integration of HL into other learning areas could help to mitigate the barrier of time. An integrated, rather than siloed approach to teaching and learning connects different areas of study simultaneously ( Moss et al , 2019 ; Minić and Jovanović, 2020 ) and facilitates meaningful learning experiences that are contextually appropriate to students ( Moss et al , 2019 ; Minić and Jovanović, 2020 ). This is particularly relevant to education that develops HL, given the contextual nature of the asset.…”
Section: Discussionmentioning
confidence: 99%
“…Some teachers suggested that integration of HL into other learning areas could help to mitigate the barrier of time. An integrated, rather than siloed approach to teaching and learning connects different areas of study simultaneously ( Moss et al , 2019 ; Minić and Jovanović, 2020 ) and facilitates meaningful learning experiences that are contextually appropriate to students ( Moss et al , 2019 ; Minić and Jovanović, 2020 ). This is particularly relevant to education that develops HL, given the contextual nature of the asset.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a lesson looking at energy density of certain foods could teach mathematical, literacy and HL skills simultaneously. Integrated teaching models have been recognised as key strategies in facilitating meaningful and contextually relevant learning experiences (Minić and Jovanović, 2020). Teachers have also confirmed that supporting an integrated approach to learning is a strength of the HealthLit4Kids program (Otten et al, 2022).…”
Section: An Ethical Evaluation Of Healthlit4kidsmentioning
confidence: 99%
“…Integrated approaches to teaching and learning have long been advocated in experiential education (Beane, 1991; Beane, 1995; Jacobs, 1989; Miller, 2006) and continue to be a recommended strategy in discussions for educational reform, to engage students with curriculums that are locally relevant and authentic (Kaufman et al, 2008; McDowall & Hipkins, 2019; OECD, 2019; Pluim et al, 2020; UNESCO, 2021). In primary education, integration is well‐established, including as a means for introducing innovation (Eteokleous‐Grigoriou & Psomas, 2013; IBO, 2014a; Lenoir et al, 2000; Minić Vesna & Jovanović Marija, 2020). However, subject integration is less common in secondary schools (Lam et al, 2013; Venville et al, 2008), the stage of schooling when students begin to encounter teachers whose pedagogy will be guided from the disciplinary perspectives of the subjects they teach (De Brabander, 2000).…”
Section: Introductionmentioning
confidence: 99%